Implementation of A Model for Cultivating Self-Reliance and Religious Values in Village Idiot Families in Ponorogo - M. Zainal Arif; Happy Susanto; Ayok Ariyanto; Adib Khusnul Rois; Syamsul Arifin (ISTAWA, 2022)
Mental retardation in the village of Karangpatihan Balong Ponorgo appears due to conditions of poverty, the cause of it all is that the community cannot access sufficient nutritious food, causing defects in the fetus and newborn. Inadequate nutritional intake in pregnant women has a close relationship with the birth of babies with mental retardation conditions. The poverty that hit Karangpatihan village is a special concern that must be resolved by the village government, an attitude of independence must be instilled in the mentally retarded community in order to overcome the poverty that occurs. The planting of independence carried out by the village government must be social and in the form of community empowerment programs in the form of making splashed batik, catfish cattle, goats and doormats. The form of religious independence of the mentally retarded community is as follows: how to make mentally retarded people have the ability to worship or religious activities, especially in ablution and congregational prayers, starting from mentoring, training, understanding until independence appears according to the abilities of each mentally retarded citizen.